Study on External Egg Quality Parameters and Hatchability of Sakini Breed in Swine and Avian Research Program, Lalitpur, Nepal (Nepalese Veterinary Journal, 2023)
Eggs are an important and convenient source of protein for those living in rural regions. In addition, eggs from local hens are popular and traded for a fair price. As a result, the primary goal of this study was to evaluate egg laying and egg quality parameters in Sakini (Gallus gallus domesticus) from Nepal in order to better understand the chicken’s reproductive fitness and the relationship between the parameters. For this, a total of 120 eggs from different weeks (30 from each week) were taken as a sample. The egg sample was collected from the birds of different ages i.e. 43rd, 48th, 56th, and 57th weeks. These chickens were raised in the same environment and management conditions at Swine and Avian Research Program (SARP), Khumaltar. Eggs were candled during incubation, i.e., on the 18th day. A strong light was held under the eggs to observe their fertility during candling of eggs. External egg quality parameters like Egg weight, Egg length, Egg breadth, Shape index and Egg color were measured. Fertility and hatchability percentages were calculated. The findings have shown that the highest fertility rate was observed for the 48.47 ±0.71 gm egg weight group i.e., 80 %. However, the highest overall hatchability was observed in the 48.73±0.68 gm egg weight group which is 70 %. On the basis of their shape index, there is significantly highest (P